Women in the thought of Imam Ali, peace be upon him A study in Nahj al-Balaghah (Journal of the College of Basic Education, 2022)
Women occupied a distinguished position in Islamic thought as a result of the reality that they experienced in the civilizations that preceded Islam, between exaltation and transcendence in some civilizations, or underestimation and inferiority in other civilizations.